Analysis of Auditor Characteristics on the Quality of Audit Results (CV. Era Digital Nusantara, 2024)
This study aims to determine and analyze the effect of independence, auditor professional skepticism, application of audit standards, audit ethics, competence and auditor role stress on the quality of audit results. The population in this study were all auditors who worked at the Supreme Audit Agency of the Republic of Indonesia Representative of South Sumatra, totaling 90 auditors. Based on this population, the sample taken using non-probability sampling with purposive sampling so that 40 auditors were obtained. The analysis technique used is multiple linear regression with hypothesis testing using the t test and F test. The results showed that independence has no effect on the quality of audit results, auditor professional skepticism has no effect on the quality of audit results, the application of audit standards has no effect on the quality of audit results, audit ethics has an influence on the quality of audit results on auditors, auditor role stress has an influence on the quality of audit results and simultaneously independence, auditor professional skepticism, application of audit standards, audit ethics, competence and auditor role stress have a significant effect on the quality of audit results. The conclusion shows that the variables of independence, professional skepticism, application of audit standards and competence have no effect on the quality of audit results on auditors of the Supreme Audit Agency (BPK-RI) Representative of South Sumatra. Only the variables of audit ethics and auditor role stress affect the quality of audit results on auditors of the Supreme Audit Agency (BPK-RI) Representative of South Sumatra. Simultaneously, the variables of independence, auditor professional skepticism, application of audit standards, audit ethics, competence and auditor role stress together have a significant effect on the quality of audit results at the BPK-RI Auditor Representative of South Sumatra.